Integrating GIS-based AHP and groundwater quality assessment to delineate groundwater potential zones in the Rontu Watershed, West Nusa Tenggara, Indonesia - Pascalia Vinca Alvando; Dede Rohmat; Faizal Immaddudin Wira Rohmat; Dasapta Erwin Irawan; Abdullah Husna; Wendi Harjupa; Fauzan Ikhlas Wira Rohmat; Mutiara Indah Nur Rohman (Results in Earth Sciences)
This study investigates the spatial distribution and quality of groundwater in the Rontu Watershed, West Nusa Tenggara, Indonesia. The analysis combines Geographic Information System (GIS)-based modeling with hydrochemical analysis. The Analytical Hierarchy Process (AHP) was employed to generate a Groundwater Potential Zone (GWPZ) map based on seven weighted parameters: geology, geomorphology, soil texture, slope, land use/land cover (LULC), lineament density, and drainage density. Sensitivity analysis revealed that slope and lithology significantly influence groundwater potential, as evident in the weighting scheme. Areas with mild topography (0°–12°) and lowland alluvial zones were found to be favorable for infiltration. The resulting GWPZ map classified the watershed into five categories, with high to very high potential zones concentrated in the northern and central parts and low potential zones found predominantly in the southeast. The high potential zone covers approximately 21 % of the study area, while the very high zone accounts for around 10 %. Groundwater quality was assessed through field measurements and laboratory analyses of physicochemical parameters, including TDS, EC, DO, pH, temperature, and major ions. Results indicate that several lowland and coastal areas exhibit elevated levels of TDS, sodium, and sulfate, which exceed national drinking water standards, potentially due to seawater intrusion and anthropogenic influence. Major ion composition further supports this finding, with dominant ion sequences of Na⁺ > Ca²⁺ > K⁺ and Cl⁻ > SO₄²⁻ > NO₃⁻. Despite this, most groundwater sources remain within sanitation quality limits. This study provides a replicable tool for groundwater development in data-limited, urbanizing regions.